Electrical conductivity, optical and metal-semiconductor contact properties of organic semiconductor based on MEH-PPV/fullerene blend - Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2008)
The electrical conductivity, optical and metal-semiconductor contact properties of the MEH-PPV:C-70 organic semiconductor have been investigated. The electrical conductivity results show that the MEH-PPV:C-70 film is an organic semiconductor. The optical band gap of the film was found to be 2.06eV and the fundamental absorption edge in the film is formed by the direct allowed transitions. The refractive index dispersion curve of the film obeys the single oscillator model and E-d and E-o dispersion parameters were found to be 10.61 and 3.89eV, respectively. The electrical characterization of the ITO/MEH-PPV:C-70 diode have been investigated by current-voltage characteristics. ITO/MEH-PPV:C-70 diode indicates a non-ideal current-voltage behavior with ideality factor n (2.50) and barrier height phi(B) (0.90eV) values. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: semiconductors; electrical properties; optical properties